2006
DOI: 10.1136/oem.2006.027748
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to asbestos and man-made vitreous fibres and risk of lung cancer: a multicentre case-control study in Europe

Abstract: In this large community-based study occupational exposure to asbestos and MMVF does not appear to contribute to the lung cancer burden in men in Central and Eastern Europe. In contrast, in the UK the authors found an increased risk of lung cancer following exposure to asbestos. Differences in fibre type and circumstances of exposure may explain these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
3
26
0
1
Order By: Relevance
“…Occupational exposures, including mainly asbestos, were estimated to account for 5-10% of male lung cancer deaths in industrialized countries, including eastern Europe [23,[26][27][28][29]. Indoor air pollution has also been a relevant lung carcinogen in western, but mostly in central and eastern Europe, with relative risks of 1.2-1.3 for solid fuel use [30].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposures, including mainly asbestos, were estimated to account for 5-10% of male lung cancer deaths in industrialized countries, including eastern Europe [23,[26][27][28][29]. Indoor air pollution has also been a relevant lung carcinogen in western, but mostly in central and eastern Europe, with relative risks of 1.2-1.3 for solid fuel use [30].…”
Section: Discussionmentioning
confidence: 99%
“…The study population includes countries that are currently among those with the highest lung cancer incidence in the world for men, with Hungary showing the worlds' highest standardized incidence ratio [8]. Tobacco consumption, other [10], polycyclic aromatic hydrocarbons [11], vinyl chloride, acrylonitrile, and styrene [12]. The analyses presented here show an elevated lung cancer risk for occupational exposure to arsenic, chromium, Linear trend p = 0.0409 p = 0.2087 a Models were adjusted for age, center, sex, tobacco consumption, and categorical variables of cumulative exposure to asbestos, silica, wood dust, and welding fumes b Models were adjusted for age, center, sex, tobacco consumption, and categorical variables of cumulative exposure to asbestos, silica, wood dust, welding fumes, nickel, chromium, and arsenic and cadmium.…”
Section: Discussionmentioning
confidence: 99%
“…This might be caused by regional quantitative and qualitative differences in exposure circumstances. In the case of asbestos, exposure circumstances could vary because of different fibre types, possibly with different carcinogenicity potential11 26 27 as well as different average concentrations and durations of exposure, and co-exposures. When the UK was excluded from the analyses, heterogeneity in risk estimates for asbestos decreased for the expert assessment (p=0.27), indicating that the UK caused most of the heterogeneity in this study for asbestos.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interpretation of the epidemiological results might well have been different because of less heterogeneous risk estimates across countries. The debate concerning country differences regarding asbestos as described by Carel and co-workers11 would not necessarily have been brought up as the argument was mostly based on the observed heterogeneity in risk estimates and absence of elevated lung cancer risk in the CEE countries associated with the predominant use of chrysotile in those countries. Recently a Canadian case–control study based on expert assessment showed an increased risk of lung cancer following asbestos exposure (OR 1.78, 95% CI 0.94 to 3.36),28 while over 90% of asbestos used in North America is chrysotile.…”
Section: Discussionmentioning
confidence: 99%